Research of Acoustic Cavitation: Results, Practical Implementation and Development Prospects - V. S. Gavriluk; N. V. Dezhkunov; A. V. Kotukhov; V. A. Koltovich; V. S. Minchuk; M. P. Fedorinchik; E. A. Kurliuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The most signiﬁcant results of research performed in the Belarusian State University University of Informatics and Radioelectronics, aimed at creating methods and instruments for monitoring cavitation and controlling its activity, are presented. To achieve this goal, it was necessary to clarify the mechanisms and patterns of new and little-studied phenomena: ultrasonic capillary eﬀect, sonoluminescence, cavitation noise and its spectral components and evaluate the possibilities of their use for hardware implementation as cavitation indicators. New cavitation phenomena have been discovered: reverse ultrasonic capillary eﬀect, generation of constant EMF under the inﬂuence of alternating pressure of ultrasonic frequency; acoustic clearing of the cavitation area with pulsed modulation of the ultrasonic ﬁeld, the eﬀect of long-term memory of the cavitation properties of the liquid. Previously unknown patterns have been established: it is shown that the cavitation region goes through four stages of development with increasing ultrasound intensity; a theorem on the maximum cavitation activity was formulated; the spectral characteristics of cavitation noise were established, correlating with the intensity of sonoluminescence. It has been shown that pulsed modulation of the ultrasonic ﬁeld makes it possible to control the dynamics of the development of the cavitation region and the activity of cavitation. Based on the data obtained, new methods and instruments have been developed to study cavitation and control its activity. In a number of parameters, the created equipment surpasses the best world samples, what is conﬁrmed by deliveries to the Russia, EU countries, China, USA and South Korea.